The nomadic life of the kazakhs (Herald of Journalism, 2019)
In the proposed article, on the basis of studying a large number of original sources, the main features of the functioning of the nomadic Kazakh society are investigated, the processes of adaptation of nomads to specific resources are analyzed. The author made an attempt to create a holistic view of the specifics of the nomadic civilization of the Kazakhs based on the analysis of a huge amount of ethnographic and historical material contained in the works of Russian scientists, travelers, officials, just witnesses and the military. A comparative analysis of the facts and data from various and numerous sources seems to the author to avoid the subjective interpretation of the questions of this study and to exclude biased judgments and conclusions. The evolutionary process of nomadism, the transformation of material culture is considered. The study of the system of material production of nomadic peoples represents a great practical sense, since they have accumulated vast experience. Of particular interest is the balanced, equilibrium state of the nomads in relation to the natural resources of the habitat. The nomadic way of life was the main ethno-integrating factor of their formation and addition to an integral socio-cultural community. In general, the available source material allowed to analyze the nomadic civilization of the Kazakhs in a reliable and complete form.
Keywords: Kazakhs, nomadic civilization, Masanov N.E., nomad.